2018
DOI: 10.3989/redc.2018.3.1532
|View full text |Cite
|
Sign up to set email alerts
|

BPMS para la gestión: una revisión sistemática de la literatura

Abstract: El objetivo de este trabajo es realizar un análisis sistemático de la literatura para mostrar el estado del arte en la investigación sobre los Sistemas de Gestión de Procesos de Negocio (BPMS, por sus siglas en inglés). Los BPMS representan una tecnología que automatiza los procesos de negocio, conectando a usuarios con sus tareas. Para ello, se realizó una revisión sistemática de la literatura de los últimos diez años, utilizando trabajos científicos indexados en las principales bases de datos del área de con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 47 publications
0
20
0
1
Order By: Relevance
“…We have used this method because this work is a synthesis of the available evidence that summarizes the information on a particular topic [24]. It is characterised by being specific, systematic, reproducible, critical and rigorous [25,26]. To carry it out, different phases have been used [24][25][26][27], as indicated below.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have used this method because this work is a synthesis of the available evidence that summarizes the information on a particular topic [24]. It is characterised by being specific, systematic, reproducible, critical and rigorous [25,26]. To carry it out, different phases have been used [24][25][26][27], as indicated below.…”
Section: Methodsmentioning
confidence: 99%
“…It is characterised by being specific, systematic, reproducible, critical and rigorous [25,26]. To carry it out, different phases have been used [24][25][26][27], as indicated below.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same way, in 2013 there is an increase in academic interest in BPMS in ports because in the context of a major economic crisis, these systems allowed greater control over business processes, great support for critical decision making, great agility and rapid adaptation to changes via restructuring and optimizating processes and greater strategic orientation to achieve business objectives (Martín-Navarro et al, 2018). In this context, BPMS allows greater control over processes.…”
Section: Number Of Publications Per Yearmentioning
confidence: 99%
“…As for theoretical research, all theoretical papers have been included, regardless of whether they are literature reviews or conceptual papers. As it occurs in BPMS research from a management perspective (Martín-Navarro et al, 2018), no quantitative empirical works analysing BPMS in ports have been found. A plausible explanation is that the nature of the object of study, the ports, makes access to large samples very difficult.…”
Section: Type Of Studymentioning
confidence: 99%